Microstructural evolution and enhanced mechanical properties of 95Al2O3–Yb/Mg/Si ceramics by optimizing sintering temperature. Issue 3 (1st February 2023) - Du, Jianzhou; Ai, Duomei; Xiao, Xin; Yang, Zirun; Zhu, Kongjun; Wang, Luming; Gu, Qilin
Abstract: Designed component of 0.95Al2 O3 –0.015Yb2 O3 –0.01MgO–0.025SiO2 (95Al2 O3 –Yb/Mg/Si) ceramics were prepared by the traditional mixed-oxide method in the sintering temperature range of 1450–1700 °C. The influence of sintering temperature on the crystal structure, densification, microstructure, mechanical, friction and wear properties of 95Al2 O3 -YbMgSi ceramics were systematically investigated. XRD and SEM analysis results revealed that the increase in sintering temperature was very beneficial to eliminate the pores, increase the density and grain size, which obeys the common grain growth law. Both the flexural strength and hardness of obtained samples were increased almost linearly when the sintering temperature increased from 1450 °C to 1700 °C. The ceramics sintered at 1650 °C showed the optimum properties: H v  = 1812.3, σ  = 151.3 MPa, μ  = 0.41, ρ  = 3.72 g/cm 3 and K c  = 8.06e −5 mm 3 /N·m, respectively. Furthermore, the results of friction and wear experiments suggested that the 95Al2 O3 –Yb/Mg/Si ceramic prepared at the optimizing sintering process exhibited more stable friction state and lower wear degree under non-lubricated conditions. The enhanced mechanical properties could be attributed to their structure densification, pore elimination and gain growth with the increase of sintering temperature.